Indications for exchange of posterior chamber phakic intraocular lens in high myopia - Priyanka Sudanaboina; Somasheila I Murthy (Indian Journal of Ophthalmology)
Purpose: To enumerate and analyze the indications for the exchange of phakic intraocular lens (pIOL) in patients with high myopia. Design: Retrospective observational case series. Methods: We retrospectively analyzed the medical reports of patients who underwent an exchange of posterior chamber pIOL at our institution between 2015 and 2022. Preoperative refractive and biometric measurements, pIOL parameters, cause for exchange, and outcomes were assessed. Results: During the study period, 1715 posterior chamber pIOL implantations were performed. Spherical pIOLs were implanted in 328 (19.1%), and toric pIOLs were implanted in 1387 (80.8%) eyes during primary surgery. Nineteen eyes from 18 patients (1.107%) required exchange. Indications for pIOL exchange included high vault in nine eyes, low vault in two, and rotation of the pIOL in five. The mean follow-up period after the pIOL exchange was 3.3 months (range: 1–6.04 months). Repeat surgery was not required for any case. None of the patients had any residual refractive error, and their best-corrected visual acuity was preserved. Conclusion: Overall, the rate of pIOL exchange in our study was low, and it is associated with good outcomes. The most common cause for exchange was high vault, followed by toric pIOL misalignment.